Effects of variability of practice in music: a pilot study on fast goal-directed movements in pianists - Bangert, Marc; Wiedemann, Anna; Jabusch, Hans-Christian (Frontiers in Human Neuroscience, 2014)
Variability of Practice (VOP) refers to the acquisition of a particular target movement by practicing a range of varying targets rather than by focusing on fixed repetitions of the target only. VOP has been demonstrated to have beneficial effects on transfer to a novel task and on skill consolidation. This study extends the line of research to musical practice. In a task resembling a barrier-knockdown paradigm, 36 music students trained to perform a wide left-hand interval leap on the piano. Performance at the target distance was tested before and after a 30-minute standardized training session. The high-variability group (VAR) practiced 4 different intervals including the target. Another group (FIX) practiced the target interval only. A third group (SPA) performed spaced practice on the target only, interweaving with periods of not playing. Transfer was tested by introducing an interval novel to either group. After a 24-hour period with no further exposure to the instrument, performance was retested. All groups performed at comparable error levels before training, after training, and after the retention interval. At transfer, however, the FIX group, unlike the other groups, committed significantly more errors than in the target task. After the retention period, the effect was washed out for the FIX group but then was present for VAR. Thus, the results provide only partial support for the VOP hypothesis for the given setting. Additional exploratory observations suggest tentative benefits of VOP regarding execution speed, loudness, and performance confidence. We derive specific hypotheses and specific recommendations regarding sample selection and intervention duration for future investigations. Furthermore, the proposed leap task measurement is shown to be (a) robust enough to serve as a standard framework for studies in the music domain, yet (b) versatile enough to allow for a wide range of designs not previously investigated for music on a standardized basis.